Expression of the estrogen and progesterone receptors as prognostic factor in serous ovarian cancers - Buchynska, L.G.; Iurchenko, N.P.; Grinkevych, V.M.; Nesina, I.P.; Chekhun, S.V.; Svintsitsky, V.S. (Experimental Oncology, 2009)
Aim: To study the expression of estrogen receptors (ER) and progesterone receptors (PR) and proliferation marker Ki-67 in ovarian tumors using immunohistochemistry, and evaluate possible prognostic significance ofthese markers. Methods: Immunohistochemical evaluation of Ki-67, ER and PR expression was performed on serous ovarian cancer (OC) tissue samples from 81 OC patients. Results: Serous OC is characterised by high proliferative activity and increased expression of steroid hormone receptors compared to nontransfomed ovarian surface epithelium. It has been shown that ER and PR expression levels depend on tumor histologic grade and the stage of the disease, and are variable between tumors of the same grade. The ER and PR expression levels correlate with OC patients’ survival. Conclusion: Proliferative activity and steroid hormone receptor status along with clinical and morphological characteristics of serous OC possess prognostic significance and may be used for evaluation of the disease course